2003
DOI: 10.1038/sj.bmt.1704319
|View full text |Cite
|
Sign up to set email alerts
|

Allogeneic bone marrow transplantation vs chemotherapy for children with Philadelphia chromosome-positive acute lymphoblastic leukemia

Abstract: Summary:Allogeneic bone marrow transplant (BMT) with an MRD in complete remission (CR)1 is the preferred treatment for children with Philadelphia-positive (Ph þ ) ALL. The role of MUD BMT in CR1 is still controversial. We compared the outcomes of two treatment strategies: BMT using an MRD or MUD vs chemotherapy in children with Ph þ ALL in CR1. In total, 21 children were treated from 1985 to 2001. In all, 10 received chemotherapy and 11 received allogeneic BMT: four MRD, seven MUD. In the MRD group, one relaps… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
18
2

Year Published

2004
2004
2013
2013

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 33 publications
1
18
2
Order By: Relevance
“…The expected risk of a serious cardiac-related event (NCI CTC grade [4][5] in the first 100 days after allo-HCT has been previously estimated at our institution to be o1%. 31 What impact imatinib therapy may have on the cardiac risk for patients undergoing a myeloablative allo-HCT has not been extensively studied.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The expected risk of a serious cardiac-related event (NCI CTC grade [4][5] in the first 100 days after allo-HCT has been previously estimated at our institution to be o1%. 31 What impact imatinib therapy may have on the cardiac risk for patients undergoing a myeloablative allo-HCT has not been extensively studied.…”
Section: Discussionmentioning
confidence: 99%
“…3 Earlier studies have shown that allo-hematopoietic cell transplant (HCT) from a matched-related donor decreases relapse rates, resulting in improved DFS to 40-60%. [4][5][6][7] At the gene level, the Ph þ chromosome is created by a translocation of the 5 0 portion of the bcr gene to the kinase domain of the abl gene, resulting in a novel fusion protein with unregulated tyrosine kinase (TK) activity. In 1999, imatinib was approved for human use as a competitive inhibitor directed toward this abl TK fusion gene found in both CML and Ph þ ALL.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4] Matched related donor stem cell transplantation (SCT) in first remission is considered the treatment of choice, with 65-83% EFS.…”
mentioning
confidence: 99%
“…More recent prospective multi-institution clinical trials corroborate the advantage of SCT. [5][6][7] Retrospective analysis did not find a better outcome for recipients of unrelated or mismatched donor SCT as compared to chemotherapy, largely because of the high TRM. However, the results for alternative donor transplantation as reported in single-center clinical trials have been better, with EFS reaching 50%.…”
Section: Sct In First Remissionmentioning
confidence: 99%